PRE-SCHOOL EDUCATION TEACHERS’ COMPETENCE DEVELOPMENT IN THE WORK WITH CHILDREN WITH SPEECH DISORDERS IN INCLUSIVE EDUCATION - Zeļenkova, Ingrīda (Education Reform: Education Content Research and Implementation Problems, 2019)
From generation to generation, there are still very topical issues affecting the education system, the quality of its performance, the methods used and the forms of organization. In the 20th century inclusive education problems were studied in Europe and the United States. Several laws have been developed that increase the ability of children with special needs to receive quality education according to their needs and abilities.There are countries where inclusive education is seen as an approach to care for disabled children. But at international level, it is seen as a reform that supports diversity among all students (UNESCO, 2001).The aim of this study is to investigate the competence of pre-school education teachers in working with children with insufficient development of the language system, to develop and approbate a program for teacher competence development.The study summarizes the questionnaire data of pre-school teachers.Quantitative and qualitative research methods were used.The research results suggest that there is a need for regular improvement of teachers' competence in working with children with insufficient development of the language system.